Estimation of the driving force acting on the interface edge - Knésl, Zdeněk; Vrbka, Jan; Vilímek, David (Computer Assisted Methods in Engineering and Science, 2023)
This paper introduces a simple and approximate method of calculating the elastic driving force acting on the interface in two-phase materials. The method is based on considerations of the elastic energy connected with the change in the shape of the interface. The two phases are considered to be elastically isotropic media with different elastic constants. The procedure is developed in the framework of the finite element method and is applied to the estimation of the local driving force in the case of the edge of an interface with a singular distribution of stress. The application of T-stress to the problem is suggested.